The risk of depression among racially diverse people living with HIV: the impact of HIV viral suppression. Issue 5 (4th May 2021) - Jain, Mamta K.; Li, Xilong; Adams-Huet, Beverley; Tiruneh, Yordanos M.; Luque, Amneris E.; Duarte, Piper; Trombello, Joseph M.; Nijhawan, Ank E.
ABSTRACT: Understanding the correlates of depression in HIV patients can help identify groups whose members are at increased risk for depression. We conducted a cross-sectional retrospective study among racially diverse, indigent patients living with HIV (PLWH) who were obtaining care in an urban safety-net hospital system and had completed a Patient Health Questionnaire-9 (PHQ-9) in 2014 or 2015. We collected demographics, HIV risk factors, HIV viral loads, CD4 counts, missed visits, and emergency department (ED) visits. Data from the Substance Abuse and Mental Illness Symptoms Screener (SAMISS) were abstracted. Missing data on substance use and CD4 cell counts were imputed to examine the odds of depression (PHQ-9 ≥ 10) by multivariable analysis for a complete case and sensitivity analysis. Stratified analysis by HIV viral suppression (VS) was used to determine the odds of depression among subgroups. Of the 5126 HIV patients (70.8% male, 56.3% Black, 44.6% MSM, 6.0% IDU), 1271 (24.8%) experienced depression (PHQ ≥ 10). In a multivariable logistic model female gender, White race, injection drug use (IDU) or men who have sex with men (MSM) as an HIV risk factor, making ≥1 ED visit, having missed any HIV visit, having AIDS, and having a positive drug screen by SAMISS increased the odds for depression. Those who had achieved HIV VS or received efavirenz had lower odds of depression. Even among those with AIDS, those failing to achieve VS were at increased odds for depression, whereas those achieving VS were not. Moderate to severe depression is prevalent among PLWH. Among those with AIDS, HIV VS modifies the odds of depression.